Clinical implementation, barriers, and unmet needs of rTMS and neuro-navigation systems in stroke rehabilitation: a nationwide survey in South Korea - Yu, Ga Hui; Park, Chulmin; Jeong, Myeong Geun; Jung, Gun Seo; Kim, Kyoung Tae (Frontiers in Neurology, 2024)
Objective The objective of this study was to determine the implementation, clinical barriers, and unmet needs of repetitive transcranial magnetic stimulation (rTMS) and neuro-navigation systems for stroke rehabilitation. Design We employed a nationwide survey via Google Forms (web and mobile) consisting of 36 questions across rTMS and neuro-navigation systems, focusing on their implementation, perceptions, and unmet needs in stroke recovery. The survey targeted physiatrists registered in the Korean Society for Neuro-rehabilitation and in rehabilitation hospitals in South Korea. Results Of 1,129 surveys distributed, 122 responses were analyzed. Most respondents acknowledged the effectiveness of rTMS in treating post-stroke impairments; however, they highlighted significant unmet needs in standardized treatment protocols, guidelines, education, device usability, and insurance coverage. Unmet needs for neuro-navigation were also identified; only 7.4% of respondents currently used such systems, despite acknowledging their potential to enhance treatment accuracy. Seventy percent of respondents identified lack of prescription coverage, time and errors in preparation, and device cost as barriers to clinical adoption of neuro-navigation systems. Conclusion Despite recognition of the potential of rTMS in stroke rehabilitation, there is a considerable gap between research evidence and clinical practice. Addressing these challenges, establishing standardized protocols, and advancing accessible neuro-navigation systems could significantly enhance the clinical application of rTMS, offering a more personalized, effective treatment modality for stroke recovery.